Endoscopic Retrofibular Groove Deepening for Management of Type A Intrasheath Peroneal Tendon Subluxation - Tun Hing Lui, M.B.B.S.(HK), F.R.C.S.(Edin), F.H.K.A.M., F.H.K.C.O.S.; Yu Hei Choi, M.BCh.B. (Arthroscopy Techniques)
In intrasheath peroneal tendon subluxation, the peroneal tendons subluxate on each other within the retrofibular peroneal tendon sheath. Two subtypes can be distinguished: type A, in which the tendons are normal, and type B, in which the peroneus brevis tendon has an associated longitudinal split and the peroneus longus tendon subluxates through this tendon split. The purpose of this technical note is to describe the details of endoscopic retrofibular groove deepening for management of type A intrasheath peroneal tendon subluxation. This can prevent extensive scar formation, tendon adhesions, and sural nerve entrapment, as well as the problem of prolonged postoperative immobilization.